Effectiveness of iron-based phosphate binders in reduction of hyperphosphataemia in chronic kidney disease patients - Pokhrel, Anil; Chand, Hema; K.C., Prabal; Shrestha, Nilasma; Ghimire, Pradeep; Ghimire, Pravesh; Adhikary, Laxman Prasad (Journal of Kathmandu Medical College, 2023)
Background: Ferric citrate is novel iron-based phosphate-binding drug for management of hyperphosphataemia and iron-deficiency anaemia in chronic kidney disease (CKD) patients. Objectives: To evaluate impact of ferric citrate therapy on reduction of phosphate levels and improvement in haematological parameters in CKD stages 3-5. Methods: This analytical, observational study was conducted at Kathmandu Medical College Teaching Hospital from 2020 July-December after ethical clearance using convenience sampling method. Non-dialysis dependent patients at CKD stages 3-5, having hyperphosphataemia (serum phosphate >=4.6mg/dL) and anaemia (serum haemoglobin <12 gm%, transferrin saturation <=30%, ferritin <=300ng/mL) were administered with 2gm twice daily dose of ferric citrate for 12 weeks and evaluated on outcomes in terms of reduction in serum phosphate levels and improvement in haematological parameters as study endpoints. Data were entered in Microsoft Excel and analysed in SPSS v.25. Significance level was set at p <0.05. Results: Of 84 study participants, majority had CKD stage 4 (46, 54.76%). A significant reduction (p <0.001) in mean serum phosphate levels of 6.21 ± 1.062 mg/dL from baseline to 4.89 ± 1.100 mg/dL in 12-weeks was observed. Patients with CKD stages 3, 4, and 5 had mean reduction of 1.67 (p = 0.005), 1.40 (p <0.001), and 1.04 mg/dL (p = 0.002) of serum Phosphate level respectively. Significant (p <0.001) improvements in hemoglobin level, serum iron, ferritin, total iron binding capacity, and transferrin saturation were reported. Conclusion: Ferric citrate is effective and well-tolerated phosphate-binder to improve hyperphosphataemia and iron deficiency anaemia in non-dialysis CKD stage 3, 4, and 5.